Coagulopathy in isolated traumatic brain injury - Boungou-Poati, Prince Darsi (My University, 2020)
Background: Although South Africa has one of the highest incidences of Traumatic Brain Injury (TBI) globally, the incidence of Traumatic Brain Injury-associated coagulopathy (TAC) and its associated risk factors in patients with isolated TBI has not been evaluated in the country. Methods: This study was conducted in the neurosurgical units at the Chris Hani Baragwanath Academic Hospital (CHBAH) and the Charlotte Maxeke Johannesburg Academic Hospital (CMJAH), over a period of 12 months. Patients admitted with isolated head injury in the neurosurgical units at the two hospitals were included. This was a cross sectional study done on the day of admission and mortality data collected on day 3. We sought to determine the incidence of coagulopathy, its risk factors and mortality outcome. Results: A total of 121 patients with isolated TBI were included. TAC occurred in 40.5% of all patients. Independent risk factors for TAC in isolated TBI were found to include a Glasgow Coma Scale(GCS) score of ≤8, presence of surface collections, midline shift, raised intracranial pressure (ICP), absent pupillary reflex, hypotension, penetrating injury and lower age. TAC patients had approximately 26 times increased odds of dying compared to those that did not have TAC (OR=26; 95 % Confidence interval (3.27 –206.5); p-value = 0.025). Conclusion: The occurrence of coagulopathy in TBI patients was high and it was a significant predictive factor for mortality. Independent risk factors for TAC in isolated TBI included a GCS score of ≤8, raised ICP, absent pupillary reflex and penetrating injury. These results are in keeping with findings in high income countries, highlighting the need for TAC to be given increased attention in the neurosurgical units in South Africa.
A research report is submitted in partial fulfilment of requirements for the degree of Masters of Medicine in Neurological Surgery to the Faculty of Health Sciences, University of Witwatersrand Johannesburg, 2020